1987
DOI: 10.1038/clpt.1987.110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food on nifedipine pharmacokinetics

Abstract: The effect of food on the bioavailability of nifedipine (Procardia), 10 mg capsules, was studied. Each of 15 male volunteers received a single oral 10 mg dose with 120 ml water under three conditions: fasting, after a low-fat (high-carbohydrate) meal, and after a high-fat meal. An open, three-way Latin-square design was employed with a 4-day washout period between administrations. Serial blood samples were collected just before the dose (0 hour) and from 0 to 8 hours after administration. Nifedipine assays wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 0 publications
3
24
1
Order By: Relevance
“…The difference between the mean and median AUC of NF in Taiwan residents indicates that the data were not normally distributed but skewed. Our data showed significantly higher values of AUC than those for the British [9][10][11][12], Americans [2,15] and Germans [4], but lower than that of Nigerians [10]. No statistical difference was seen when compared with Indians [9], Mexicans [7,16] and Japanese [17] after the NF dose was normalized.…”
Section: Discussioncontrasting
confidence: 74%
“…The difference between the mean and median AUC of NF in Taiwan residents indicates that the data were not normally distributed but skewed. Our data showed significantly higher values of AUC than those for the British [9][10][11][12], Americans [2,15] and Germans [4], but lower than that of Nigerians [10]. No statistical difference was seen when compared with Indians [9], Mexicans [7,16] and Japanese [17] after the NF dose was normalized.…”
Section: Discussioncontrasting
confidence: 74%
“…The same findings were observed for the other dihydropyridine calcium antagonists as benidipine (16), felodipine (17), and nisoldipine (16), showing the same lipophilicity as manidipine (18). On the other hand, no significant food effect on the extent of absorption was observed for other less lipophilic dihydropyridine calcium antagonists as nifedipine (19,20,21,22,23), amlodipine (24,25,26), isradipine (27), and nilvadipine (28).…”
Section: Pharmacokinetics Of Manidipinesupporting
confidence: 58%
“…The first was carried out in patients with myocardial infarction where it was found that taking nifedipine following a light breakfast delayed both the rate of absorption and the peak concentration achieved (Hirasawa et al, 1985). Both the delay in achieving maximum concentration and the reduction in peak concentration when a nifedipine capsule is taken following food were confirmed in normal volunteers (Challenor et al, 1987;Reitberg et al, 1987). Recently, a 'biphasic' formulation of nifedipine has been developed which contains 5 mg 'rapid' release and 15 mg 'retarded' release drug.…”
Section: Introductionmentioning
confidence: 99%